IMPLEMENTASI KEBIJAKAN VAKSINASI COVID-19 DI PUSKESMAS KEDUNGDORO KECAMATAN TEGALSARI KOTA SURABAYA - Ruli Ani Siregar; Indah Prabawati (Universitas Negeri Surabaya, 2022)
The Indonesian government issued a COVID-19 vaccination policy as an effort to overcome the Covid-19 problem. The Kedungdoro Health Center is one of the health facilities located in the city center with a dense level of community mobility. With the density of mobility, group immunity is needed to overcome the spread of the Covid-19 virus by vaccinating against Covid-19. The purpose of this study is to describe the implementation of the Covid-19 Vaccination Policy at the Kedungdoro Health Center as an effort to protect themselves from the covid-19 virus by usingindicators content of policy and context of policy. The research method used is a qualitative approach research method with descriptive research type. Data collection techniques used are participant observation, in-depth interviews, and documentation. The results of the study were based on indicators of content of policy, namely the benefits of a vaccination policy being able to reduce cases of positive patients and deaths due to COVID-19 at the Kedungdoro Health Center. This is also driven by the role of good program implementers and sufficient resources. The obstacles encountered were the level of community compliance was still lacking due to fear of needles, fear of comorbid patients, and doubts about the effectiveness of vaccines due to the spread ofnews hoax. Meanwhile, inindicators context of policy, the strategies used are socialization, creatinggroups WhatsApp, door to door and vaccination monitoring throughapplications Pcare and Smile. The vaccination process carried out by the Kedungdoro Health Center was in accordance with technical instructions, but there was a lack of preparation in its implementation. The researcher's suggestion is that the puskesmas carry out routine socialization more deeply by explaining the contents of policies that regulate vaccination to convince the public regarding the importance of covid-19 vaccination accompanied by monitoring the spread ofnews hoax. Keywords: Policy Implementation, Vaccination, Covid-19.